Where, when and what? A time study of surgeons' work in urology. - Jan Wolff (Public Library of Science (PLoS), 2014)
Introduction Staff time is a relevant resource in the delivery of health care interventions. Its measurement is a prerequisite for unit costing but usually complex. The aim of this study was to analyse the distribution of surgeons' work time among types and places of activities. A second aim was to use these data to calculate costs per unit of output. Methods A self-reporting work sampling study was carried out at a department of Urology. All of twelve surgeons involved in clinical care participated in a two-week analysis of their work time. Results A total of 2,485 data-points were collected, representing about 1,242 hours of work time. Surgeons spent the greater part of their work time in direct patient care, but substantial shares were required for documentation and organisation. Assistants were mainly required at the wards and consultants at the operating theatre and the outpatient unit. Staff costs of surgeons were 32 € and 29 € per patient day at the wards, respectively, 1.30 € per minute at the operating theatre and 32 € per visit at the outpatient unit. Conclusion Results provided a basis for costing of health care interventions at the study site. However, future research should focus on the establishment of standardised terminology in order to increase transferability of results.